A transferable vehicle energy consumption evaluation framework for quantifying vehicle electrification energy benefits - Zhenyu Jia; Zeping Cao; Jiawei Yin; Lin Wu; Ning Wei; Yanjie Zhang; Zhiwen Jiang; Qijun Zhang; Hongjun Mao (npj Sustainable Mobility and Transport)
Abstract Vehicle electrification is a major strategy by China to reduce energy consumption and emissions. However, it is difficult to quantify the energy advantages of EVs, especially in cross-regional comparisons. Based on the 3-D markov chain and machine learning methods, this study proposes a framework to evaluate energy consumption benefits and validates it with data from two cities with distinct geographical features, Tianjin and Xining. The results show that EVs can achieve energy consumption benefits from 16.4% to 77.8%. While EVs have significant energy consumption benefits, there are regional differences. Compared to internal combustion engine vehicles, battery EVs showing greater benefits in Tianjin and plug-in hybrid EVs in Xining. The model interpretation indicates that the difference stems from Tianjin’s more frequent and intense deceleration and Xining’s more varied terrain. A standardized energy consumption evaluation framework that integrates regional and vehicle type differences is essential to the EVs’ promotion.